Floating Solid Particles Interacting with Tilted Square Obstacles in Fluid Affecting Drag Forces (Advances in Applied Mathematics and Mechanics, 2022)
We have analyzed the kinetics of solid circular particles interacting withfluid, outer boundary and internal square shaped obstacles tilted at a $45^{°}$ angle. Theeffects on the motion of particle due to collision with obstacles and wall are inspected.An Eulerian approach is used to study the behavior of particle in the fixed computational mesh. The interactions between fluid, particles and obstacles have been carriedout in the whole domain by using fictitious boundary method (FBM). In this work, theparticulate flow simulations are computed by using finite element solver FEATFLOW.Numerical results are presented by assigning different alignments to the obstacles andvarying their positions in the domain. Particle-wall, particle-particle and particle-obstacle collisions are treated by applying a modified collision model proposed byGlowinski et al. The rapid change in drag forces acting on obstacles due to nearbypassing particles and its effect on the fluid motion has been investigated.